Kesetaraan Gender Dalam Mengontrol Kemampulabaan Dan Efisiensi Pada Struktur Kepemilikan Perusahaan - Ardana Putra, I Nyoman Nugraha; Santoso, Budi; Sakti, Dwi Putra Buana (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2023)
Gender has become quite an interesting and unique topic of conversation from time to time. The pros and cons behind gender equality are never ending and can be thoroughly discussed from various perspectives. If viewed from an ownership perspective, this is closely related to supervisory ability which is studied through gender. So far, ownership structure has long been used as a proxy for good corporate finance (GCG). Apart from that, according to agency theory, the ownership structure is considered capable of preventing and eliminating agency costs. This research is a comparative study that compares People's Economic Banks (BPR) which are owned by women with BPRs owned by men only (which do not have a female composition). The research was conducted at BPR in West Nusa Tenggara (NTB) Province. The analytical tool used is the t test (difference test) with two independent samples. The results show that there is no difference in profitability and efficiency in terms of gender. This research provides recommendations for companies to consider the presence of women as an important resource in the decision-making process and efforts to improve business performance.